DIGITALISASI HADIS (Studi Hadis di Era Digital) - Siti Syamsiyatul Ummah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
As the second sourceof Islamic teaching after the Qur’an, the study of the hadis continued to be developed increasingly against the rapidly growing age of technology marked by the development of technology as one of the tools of information and communication in the global era. Accordingly, hadis were developed to balance and adapt to the present digital age. Access to the hadis that used to be obtained manually has now been accessed through the internet software/ applications. As the Maktabah Syamilah, the Lidwa Pusaka, the Jawami’ al-Kalim and so on. With this development, it is expected that society in special millennial generations use the software provided as the digitization forms of the hads to be used as best possible. So the essence of hadis doesn’t fade or fade in the midst of today’s modern society.